Behaviour of ring bivalents in holokinetic systems : Alternative sites of spindle attachment in Pachylis argentinus and Nezara viridula (Heteroptera) - Papeschi, Alba G. (2003)
Heteropteran chromosomes are holokinetic; during mitosis, sister chromatids segregate parallel to each other but, during meiosis, kinetic activity is restricted to one pair of telomeric regions. This meiotic behaviour has been corroborated for all rod bivalents. For ring bivalents, we have previously proposed that one of the two chiasmata releases first, and a telokinetic activity is also achieved. In the present work we analyse the meiotic behaviour of ring bivalents in Pachylis argentinus (Coreidae) and Nezara viridula (Pentatomidae) and we describe for the first time the chromosome complement and male meiosis of the former (2n=12+2m+X0, pre-reduction of the X). Both species possess a large chromosome pair with a secondary constriction which is a nucleolus organizer region as revealed by in-situ hybridization. Here we propose a new mode of segregation for ring bivalents: when the chromosome pair bears a secondary constriction, it is not essential that one of the chiasmata releases first since these regions or repetitive DNA sequences adjacent to them become functional as alternative sites for microtubule attachment and they undertake chromosome segregation to the poles during anaphase I.